Proposição de lista de avaliação de dispositivos visuais em canteiros de obras - Abid Neto, Said (2020)
The objective of visual management is commonly related to the increase in visual communication, whose consequence is an increase in transparency. As a result, losses can be reduced, and productivity increased. However, visual management is still relatively limited in industrial assembly construction sites. Moreover, there is a lack of understanding on how to evaluate the visual devices used in this context. Therefore, this study aims to develop a method to evaluate the visual devices present in an industrial assembly construction site. This research proposes applying an evaluation list for visual devices at construction sites based on Galsworth’s taxonomy (1997), dividing visual devices into four categories of level of control, namely: indicators, flags, controllers, and guarantors. In addition, it proposes a taxonomy related to the purpose of the device, namely: space, organization and movement, production and health, safety, and environment. The proposed evaluation list was applied to five different industrial assembly construction sites of a given company. The adopted methodological approach was Design Science Research and developed the artifact. Furthermore, the practical knowledge obtained through visits to construction sites was also employed. The results showed that applying the evaluation list on construction sites is feasible, but it depends on the evaluator’s skill and understanding of the visual devices. Nevertheless, the practical situations can be related to best practices, serving as a parameter for the continuous improvement of the company as well as for application in other construction companies. The study's main contribution was elaborating the proposed evaluation list, which can be used both by researchers and companies that intend to evaluate the visual devices used in construction sites. In addition, the classification of visual devices regarding their taxonomy and the results of the evaluations of visual devices in the studied sites stand out as theoretical contributions.